Elevated Siglec-7 expression correlates with adverse clinicopathological, immunological, and therapeutic response signatures in breast cancer patients - Benthami, Hamza; Zohair, Basma; Rezouki, Ibtissam; Naji, Oumayma; Miyara, Kenza; Ennachit, Simohamed; Elkarroumi, Mohamed; Aschawa, Hind; Badou, Abdallah (Frontiers in Immunology, 2025)
IntroductionBreast cancer is a highly heterogeneous malignancy, characterized by an intricate, hypersialylated tumor microenvironment that actively inhibits immune functions. Although immune checkpoint inhibitors have marked clinical advantages in various tumor types, their efficacy in Triple-Negative Breast Cancer (TNBC) and Human Epidermal Growth Factor Receptor 2 positive (HER2+) patients remains limited. Siglec-7 has emerged as a novel and promising candidate for advancing cancer immunotherapy. MethodsHerein, we explored the potential role of Siglec-7, a key inhibitory glycoimmune checkpoint, in human breast tumor microenvironment in a cohort of 45 Moroccan patients. Subsequently, data were corroborated using large-scale data from independent cohorts of American and British-Canadian patients, the TCGA and METABRIC. ResultsWe report that Siglec-7 transcripts were significantly upregulated in breast tumor tissues compared to matched adjacent non-invaded tissues. Furthermore, higher Siglec-7 expression correlated with poor clinicopathological features, including negative Estrogen Receptor (ER) and Progesterone Receptor (PR) status, advanced tumor grades, and unfavorable patient prognosis. Siglec-7 overexpression was linked to gene expression patterns, known to promote breast tumor progression through pathways involved in proliferation, invasion, and immune escape. Notably, high Siglec-7 expression was associated with increased infiltration of immunosuppressive cells and T-cells with an exhausted phenotype. Interestingly, a positive correlation between siglec-7 and A2AR, another emerging and potent inhibitory checkpoint, was revealed, along with the co-upregulation of other inhibitory immune checkpoint genes; and this was associated with signatures of impaired immune effector functions. Finally, our data also pinpointed an interesting role of high Siglec-7 expression in predicting resistance to conventional therapies, including chemotherapy, endocrine treatments, and immunotherapy.DiscussionThese findings strongly suggest a central role for Siglec-7 as a promising therapeutic target and prognostic biomarker for human breast cancer, warranting further investigation into its clinical potential.